Platelets regulate CD4+ T-cell differentiation via multiple chemokines in humans - Gerdes, Norbert; Zhu, Linjing; Ersoy, Maria; Hermansson, Andreas; Hjemdahl, Paul; Hu, Hu; Hansson, Göran K.; Li, Nailin (Thrombosis and Haemostasis, 2011)
Atherosclerosis is an inflammatory and thrombotic disease. Both platelets and lymphocytes play important roles in atherogenesis. However, information on their interaction is limited. We therefore studied how platelets regulate CD4+ T cell activation and differentiation. Human CD4+ T cells and autologous platelets were co-cultured. Platelets concentration-dependently enhanced anti-CD3/CD28-induced IFNγ production by CD4+ T cells, but attenuated their proliferation. Abrogation of heterotypic cell-cell contact partially reversed the enhancement, and supernatant from activated platelets partially mimicked the enhancement, suggesting that platelets exert their effects via both soluble mediators and direct cell-cell contact. Platelets enhanced the production of IL-10 and cytokines characteristic for type 1 T helper (TH1) (IFNγ/ TNFα) and TH17 (IL-17) cells, but influenced TH2 cytokines (IL-4/IL-5) little. The cytokine responses were accompanied by enhanced TH1/TH17/TReg differentiation. Using neutralising antibodies and recombinant PF4, RANTES, and TGFβ, we found that platelet-derived PF4 and RANTES enhanced both pro- and anti-inflammatory cytokine production, whilst recombinant TGFβ enhanced IL-10 but not TNFα production. In conclusion, platelets enhance the differentiation and cytokine production of anti-CD3/CD28-stimulated CD4+ T cells via both multiple chemokines and direct cell-cell contact. Our study provides new insights into the cross-talk between thrombosis and adaptive immunity, and indicates that platelets can enhance T-effector cell development.
Keywords: Platelets; CD4+ T cells; regulatory T cells; TH17 cells; adaptive immunity